Radioactive 131Iodine body burden and blood dose estimates in treatment for differentiated thyroid cancer by external probe counting - Ravichandran, Ramamoorthy; Al Balushi, Naima (World Journal of Nuclear Medicine, 2016)
Radioactive131 iodine (RAI) body burden is estimated in thyroid cancer patients by a) exposure rate meter and b) external probe counting. A calibration factor of 301 cpm/MBq (d = 16 cm) is used for the probe for estimates of whole body activity. Patients sit in a rotating stool with their center corresponding to the field of view for estimation of whole body RAI. Radioactive counts are obtained foranterio posterior (AP) and postero anterior (PA) geometries. Whole body retention factor is expressed as a ratio against assayed activity administered to the patient on day 1. With exposure rate measurement, for off-thyroxin (hypothyriod) patients, the retention factors were 0.148 ± 0.12 (n = 211) and 0.07 ± 0.08 (n = 68) at 48 h and 72 h, respectively. For recombinant TSH (rhTSH) (euthyroid) group, the retention factors were 0.089 ± 0.06 (n = 24) and 0.05 ± 0.05 (n = 19) at 48 h and 72 h, respectively. By probe counting method, the obtained retention factors were 0.081 ± 0.013 (range: 0.071-0.096) (off-thyroxine group) and 0.039 ± 0.03 (range: 0.008-0.089) for the rhTSH group at 48 h. The 72 h retentions in the off thyroxine (hypothyriod) group and the rhTSH (euthyroid) group were 0.048 ± 0.024 (range: 0.016-0.076) and 0.005, respectively. The radioactive body burdens at 48 h were in the range of 290-315 MBq (7.8-8.5 mCi) for the off-thyroxine group and 44-286 MBq (1.2-7.7 mCi) for the rhTSH group. The calculated residence times in whole body were 21.97 ± 3.8 h (range: 17.1-27.1) for off-thyroxine group and 14.28 ± 2.75 h (range: 9.97-19.46) showing high statistical significance (P < 0.001). The specific blood doses were 0.118 ± 0.025 mGy/MBq (range: 0.083-0.172) for the off-thyroxine group (females n = 23); 0.87 ± 0.028 mGy/MBq (range: 0.057-0.130) (females n = 13), 0.080 ± 0.013 mGy/MBq (range: 0.069-0.098) (males n = 5) and 0.080 ± 0.028 (range: 0.059-0.118 for rhTSH patients (males n = 4). The mean mGy/MBq for blood was higher in females--about 10% for the rhTSH group compared to 40% higher for the off thyroxine (THW) group. The dose to blood was "inversely proportional" to the body weight, both in the off-thyroxine group and the rhTSH group but the dependence was not very strong with rhTSH administration because of less residence time of the radioactive iodine. There was no correlation between administered activity and retained body burden at 48 h or 72 h.
Keywords: Blood dose in iodine 131; differentiated thyroid cancer; iodine kinetics; radioactive iodine; whole body retention